Adsorption and Co-Adsorption of Polyaldehyde Dextran Nanoparticles and Nonionic Surfactant at an Air–Water Interface: Potential Implications for Pulmonary Drug Delivery - Jabłczyńska Katarzyna; Sosnowski Tomasz R. (Chemical and Process Engineering)
Measurements of dynamic surface tension were carried out in aqueous systems (water or 0.1 mM Triton X-100) comprising nanoparticles formed from chemically modified polyaldehyde dextran (PAD). The nanostructures, considered as potential drug carriers in aerosol therapy, were obtained from biocompatible polysaccharides by successive oxidation and reactive coiling in an aqueous solution. The dynamic surface tension of the samples was determined by the maximum bubble pressure (MBP) method and by the axisymmetric drop shape analysis (ADSA). Experiments with harmonic area perturbations were also carried out in order to determine surface dilatational viscoelasticity. PAD showed a remarkable surface activity. Ward-Tordai equation was used to determine the equilibrium surface tension and diffusion coefficient of PAD nanoparticles (D = 2.3×10-6 m2/s). In a mixture with Triton X-100, PAD particles showed co-adsorption and synergic effect in surface tension reduction at short times (below 10 s). Tested nanoparticles had impact on surface rheology in a mixed system with nonionic surfactant, suggesting their possible interactions with the lung surfactant system after inhalation. This preliminary investigation sets the methodological approach for further research related to the influence of inhaled PAD nanoparticles on the lung surfactant and mass transfer processes in the respiratory system.